EXSPRESSION OF MDR-GENES AND MONORESISTANCE GENES IN NON-SMALL-CELL LUNG CANCER - E. L. Yumov; М. М. Tsyganov; N. V. Litviakov; T. V. Polishchuk; S. V. Miller; S. A. Tuzikov (Сибирский онкологический журнал, 2016)
We studied the expression of multidrug resistance genes (MDR) and monoresistance genes in normal bronchial tissue and tumor tissue of the non-small cell lung cancer (NSCLC) after neoadjuvant chemotherapy (NACT) (vinorelbine-carboplatine). The study included 30 patients with NSCLC (Т2–4N0–3M0)). Normal bronchial tissue, normal lung tissue and tumor tissue collected during surgery following neoadjuvant chemotherapy (NACT) served as a material of the study. The expression levels of MDR genes (ABCB1, ABCB2, ABCC1, ABCC2, ABCС5, ABCG1, ABCG2, GSTP and MVP, and monoresistance genes (BRCA1, ERCC1, RRM1, TOP1, TOP2A, TUBB3 and TYMS) were estimated by quantitative reverse transcriptase PCR (RT-qPCR). The expression levels of some MDR genes and monoresistance genes (АВСВ1, АВСВ2, ABCG1, ERCC1, GSTP1 and MVP) were significantly higher in the bronchi than in tumor tissue. The expression of ABCG1, ABCG2 and ERCC1 genes was higher in patients with T1-2 cancer than in patients with T3-4 cancer. Patients with adenocarcinoma had higher expression of BRCA1, MVP and ABCB1 genes than patients with squamous cell lung cancer. A tendency towards reduction in the expression level of MDR-genes and monoresistance genes was observed in patients with partial tumor regression compared to that observed in patients with stable disease. These findings were consistent with the previous data on reduction in the MDR-gene expression after chemotherapy with a good response in breast cancer patients.